Molecular detection of Helicobacter pylori and clarithromycin resistance in gastric biopsies: a prospective evaluation of RIDA®GENE Helicobacter pylori assay. Issue 3 (4th May 2021) - Van den Poel, Bea; Gils, Sarah; Micalessi, Isabel; Carton, Saskia; Christiaens, Paul; Cuyle, Pieter-Jan; Moons, Veerle; Van Olmen, Gust; Smismans, Annick; Bourgain, Claire; Bossuyt, Peter; Frans, Johan
ABSTRACT: Background : Empirical treatment of Helicobacter pylo ri (HP) depends on the local prevalence of clarithromycin resistance but data are lacking and culturing of HP is time-consuming. We evaluated RIDA®GENE Helicobacter pylori assay (r-biopharm), a quantitative PCR assay for detecting HP and clarithromycin resistance mutations in gastric biopsies. Material/methods : Gastric biopsies were obtained from each of 436 consecutive patients referred for gastroscopic investigation and results of qPCR were compared to culture and immunohistochemical staining (IHCS). Results : Of 436 samples, 47 were positive for HP by PCR (11%), 42 by culture (9.7%) and 44 by IHCS (10%). Compared to culture, sensitivity and specificity of the qPCR were 100% and 99%, respectively, and 96% and 99% compared to IHCS. The sensitivity and specificity for clarithromycin resistance detection were 92% and 97%, respectively. Conclusions : RIDA®GENE Helicobacter pylori assay reliably and rapidly detects HP and its resistance to clarithromycin in human gastric biopsies.